CO21 | Viscoelastic testing in inherited bleeding disorders: a cross-sectional comparison between viscoelastic coagulation monitoring (VCM) and rotational thromboelastometry (ROTEM) (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Congenital bleeding disorders show complex haemostatic defects that routine assays overlook. Viscoelastic Coagulation Monitoring (VCM, native whole blood) and Rotational Thromboelastometry (ROTEM, citrated whole blood) provide dynamic clot assessment but are still little used bedside. We compared the two platforms in a group of patients with congenital bleeding disorders and healthy controls, and explored their sensitivity to FVIII levels in haemophilia A (HA), to build baseline data for future acute-bleeding studies.